Economic metaphors in the Peruvian print media: a study of the column “Opinion” in the weekly newspaper Hildebrandt en sus Trece - Huamán Neyra, Víctor Hugo (2021)
This research suggests a linguistic approach based on cognitive semantics. The study material comes from the national print media such as weekly newspapers. The edition prints are issued once a week and the name of this publication is Hildebrandt en sus Trece. We will analyze the conceptual metaphors related to the economic field. We have only selected the Opinion section by the economist Pedro Francke. Cognitive semantics presupposes the production and presence of metaphors in all production writings where people cognitively develop internal schemes for the comprehension of meanings.